Islamic Religious Education Teachers in Building Anti-Bullying School Culture - Arif Rahman Hakim; Muhammad Hasyim; Ahmad Budiyono; Hani Adi Wijono (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
Bullying has become a persistent challenge in educational environments, affecting students’ psychological well-being, social relationships, and academic development. In response to increasing concerns regarding school violence and student morality, the role of Islamic Religious Education (PAI) teachers in fostering character development and preventing bullying has gained growing attention. This study aims to analyze the role of PAI teachers in building an anti-bullying school culture at SMP Negeri 5 Jombang. This research employed a qualitative case study approach. Data were collected through interviews, observations, and documentation involving PAI teachers, counseling teachers, school administrators, and students. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. The findings reveal that PAI teachers play strategic roles as moral educators, spiritual mentors, and social role models in preventing bullying through religious guidance, emotional mentoring, moral habituation, and character education programs. Religious activities such as congregational prayers, Qur’anic recitation, istighosah, and Islamic spiritual programs contribute significantly to strengthening students’ empathy, emotional discipline, tolerance, and social awareness. The study also found that bullying prevention becomes more effective when supported through collaboration among PAI teachers, counseling teachers, school administrators, and parents. However, challenges related to digital media exposure, peer-group influence, and limited parental supervision continue to affect students’ behavior.This study contributes to the growing discourse on religion-based bullying prevention and highlights the importance of integrating moral internalization, emotional guidance, and collaborative educational approaches in creating sustainable anti-bullying school cultures.